DOI: 10.15368/theses.2010.49
|View full text |Cite
|
Sign up to set email alerts
|

An Investigative Study Into the Relationship of Bone Morphogenetic Protein Antagonist Expression and Osteocyte Density by Region and Quadrant

Abstract: The role of cytokines and cell behavior and viability with respect to bone remodeling and bone behavior is an exciting area of orthopedic research. The purpose of this study was to investigate the relationships between BMP antagonist expression and osteocyte density, lacunar densities and osteocyte viability in cortical bone. Samples of unloaded tibial bone obtained from six C57Bl/6 mice were immunohistochemically stained for gremlin and noggin expression and also underwent methyl green staining to determine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 56 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Coincidentally, in Mosher's previous study, the midshaft region demonstrated higher gremlin expression than both the proximal and distal regions as well (Mosher 2010). This indicates some relationship between BMP antagonists and apoptotic osteocytes that is confirmed by the regression analysis.…”
Section: Regional Analysismentioning
confidence: 53%
See 3 more Smart Citations
“…Coincidentally, in Mosher's previous study, the midshaft region demonstrated higher gremlin expression than both the proximal and distal regions as well (Mosher 2010). This indicates some relationship between BMP antagonists and apoptotic osteocytes that is confirmed by the regression analysis.…”
Section: Regional Analysismentioning
confidence: 53%
“…No quadrantal differences were seen in the percentage of apoptotic osteoctyes, total lacunar density, viable osteocyte density, and percentage of viable osteocytes as well. Mosher's study showed similar results with no differences between quadrants with respect to viable osteocyte density, total lacunar density, percentage of viable osteocyte, and gremlin expression (Mosher 2010). This overall lack of variation among quadrants is not uncharacteristic of unloaded bone conditions.…”
Section: Quadrantal Analysismentioning
confidence: 58%
See 2 more Smart Citations